Personal de enfermería contagiado por COVID-19: condiciones de trabajo y sus factores asociados en tres hospitales de Lima-Perú - Orfelina Arpasi Quispe; Gaby Sonia Chávez Zegarra; Lili Albertina Fernández Molocho; Willy Jhon Medina Bacalla; Zoila Esperanza Leitón‐Espinoza; Vilanice Alves de Araújo Püschel; Jack Roberto Silva Fhon (My University, 2022)
Objective: To determinate the prevalence of COVID-19 in the nursing personnel, working conditions, and their associated factors in three hospitals in Lima-Peru.Method: A quantitative, descriptive cross-sectional study of the web survey was carried out between November 2020 and February 2021 with 495 nursing personnel members from the three public hospitals in Lima. Results: 63% of the participants were from the Guillermo Almenara Irigoyen National Hospital, 20% from the San Isidro Labrador Hospital, and 17% from the II Vitarte Hospital. The prevalence of COVID-19 in the nursing personnel was 47.3%. When analyzing the demographic characteristics of the participants, a significant association of the education variable with the disease was evidenced (OR=1.50, p =0.04), showing that those with higher education are 1.5 times more likely to develop COVID-19 compared to those with postgraduate studies; the variables related to working conditions and risk factors did not show a significant association (p>0.05) with the disease.Conclusions: Except for education, there is insufficient evidence to affirm a significant association of COVID-19 with demographic characteristics, work-related variables, and those considered a risk. This research makes significant contributions to nursing practice, research, and teaching. Objetivo: Determinar la prevalencia de la COVID-19 en el personal de enfermería, las condiciones de trabajo y sus factores asociados en tres hospitales de Lima-Perú.Método: Estudio cuantitativo, descriptivo de corte transversal del tipo web-survey realizado entre los meses de noviembre 2020 a febrero de 2021 con la participación de 495 integrantes del personal de enfermería de tres hospitales públicos de la ciudad de Lima. Resultados: El 63% de los participantes fueron del Hospital Nacional Guillermo Almenara Irigoyen, 20% del Hospital San Isidro Labrador, y 17% del Hospital II Vitarte. La prevalencia de la COVID-19 en el personal de enfermería fue de 47.3%. Al analizar las características demográficas de los participantes se evidenció asociación significativa de la variable escolaridad con la enfermedad (OR=1.50, p=0.04), mostrando que los que cuentan con estudios superiores tienen 1.5 veces mayor probabilidad de desarrollar la COVID-19 frente a los que poseen estudios de posgrado; las variables relacionadas con las condiciones de trabajo y factores de riesgo no evidenciaron asociación significativa (p>0.05) con la enfermedad.Conclusiones: A excepción de la escolaridad no existe evidencia suficiente para afirmar asociación significativa de la COVID-19 con las características demográficas, las variables relacionadas al trabajo y las consideradas como riesgo. La investigación aporta contribuciones importantes a la práctica, la investigación y la docencia en enfermería.
Keywords: Coronavirus disease 2019 (COVID-19); Medicine; Nursing; University hospital; Demography; Humanities; Disease; Family medicine; Sociology; Infectious disease (medical specialty); Philosophy; Pathology; Coronavirus disease 2019 (COVID-19); Medicine; Nursing; University hospital; Demography; Humanities; Disease; Family medicine; Sociology; Social Sciences Psychology Social Psychology Stress and Burnout Research; Social Sciences Economics, Econometrics and Finance Economics and Econometrics Business, Innovation, and Economy; Physical Sciences Environmental Science Health, Toxicology and Mutagenesis Public Health and Environmental Issues